Annual survey of English law 1932 - London School of Economics and Political Science. Department of Law. (London : London school of economics and political Science (University of London) Dept. of Law., 1933)
Each subdivision includes sections "Legislation", "Case law" and "Literature."
Also available in print.
Keywords: Law -- Great Britain; Electronic journals